Effect of Irrigation Regime On Yield and Water Productivity of Maize (Zea Mays) in the Lake Tana Basin, North West Ethiopia - Amare Tsige Genet; Dires Tewabe; Atalktie Abebe; Alebachew Enyew; Mulugeta Worku (Turkish Journal of Agriculture: Food Science and Technology)
Proper scheduling gave water to the crop at the right time in the right quantity to optimize production and minimize adverse environmental impact. Therefore, the objective of this study is to quantify the effects of irrigation regimes on yield and yield components of Maize in the Lake Tana basin during 2016-2018. CROPWAT 8.0 model was used to determine the crop water requirement. Almost all parameters were adopted the default value of CROPWAT 8.0. Field data including; field capacity (FC), permanent wilting point (PWP), initial soil moisture depletion (%), available water holding capacity (mm/meter), infiltration rates (mm/day), and local climate data were determined in the study area. The treatments were arranged in factorial combinations with five irrigation depths (50, 75, 100, 125 and 150% of ETc) and two irrigation intervals (14 and 21 days) laid out in a randomized complete block design with three replications. The result was analyzed using SAS 9 software and significant treatment means separated using least significant difference at 5%. The result showed that the interaction of irrigation depth and irrigation frequency has no significant effect on the average grain yield and water use efficiency of maize. At koga, the highest grain yield (7.3 t ha-1) and water use efficiency (0.9 kg m-3) obtained from 100% ETc. while, at Ribb the highest grain yield (10.97 t ha-1) and water use efficiency (1.9 kg m-3) obtained from 21 days irrigation interval. Therefore, for Koga and similar agro ecologies maize can irrigated with 562 mm net irrigation depth and 21-day irrigation interval and at Rib and similar agro ecologies maize can irrigated with 446.8 mm net irrigation depth and 21- days irrigation interval.